Advanced Public Procurement as Industrial Policy The Aircraft Industry as a Technical University - Eliasson, Gunnar; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
The primary theme of this book is to investigate the macroeconomic significance of the "cloud" of technological spillovers that surrounds advanced industrial production: In what ways do technological innovations spread and contribute to economic growth? What policies can be developed to maximize the economic potential of innovations? These themes are particularly timely in the context of global economic crisis, government-sponsored stimulus packages, and the ongoing evolution from manufacturing-based to knowledge-based economies. To explore these issues in depth, Gunnar Eliasson focuses on a detailed case study of the development of Saab$1 (Bs military aircraft, the JAS 39 Gripen system$1 (Ba project that involves advanced technological innovations, a complex network of suppliers, public-private sector collaboration, and both military and commercial applications. The experience in the aircraft industry is also compared with spillover effects in telephony, computers, and medical technologies. The study emphasizes the role of customer competence in raising the quality of innovation supply, and of entrepreneurship and industrially competent venture capital for commercializing spillovers. Eliasson integrates micro-econometrics and case study analysis with macroeconomics, innovation study methods, and business administration theory to measure the effects of technology spillovers and generate a solid empirical foundation for policy analysis. In particular, he considers: the role of competent public (government) procurement as a new demand policy to support innovation supply the emergence of the advanced firms as "technical university," where continual learning takes place and entrepreneurship among customers and other stakeholders is encouraged issues of intellectual property rights and the social value of technological innovations the implications for strategic business practice and public policy The result is a book that will appeal to a broad spectrum of academics, industry leaders, and policymakers interested in the dynamics of innovation supply, commercialization of technologies and economic growth.s
On the Cloud of Technology that Surrounds Advanced Production: A Summary of Results -- The Art of Defining, Pricing, and Marketing Advanced Multidimensional Products that Spill Technology -- Spillovers and Innovative Technology Supply: A Literature Survey -- Capturing the Direct and the Serendipitous Spillovers: The Case of Sweden$1 (Bs Military Aircraft Industry -- Looking into the Future on JAS Gripen Spillovers -- Saab in South Africa: Technology Transfer to an Industrializing Economy -- The European Policy Perspective -- Private and Social Spillover Benefits from Advanced Procurement: Defining and Estimating the Spillover Multiplier -- Advanced Purchasing as Industrial Policy: On the Advanced Firm as a Technical University.s
Keywords: Economics; Industrial organization (Economic theory).; Industrial procurement; Technology; Economics/Management Science; R & D/Technology Policy; Technology Management; Procurement; Industrial Organization